(untitled) (Historia, 2021)
Uncertainty in connection with the covenant of 1838. Aspects of the Voortrekkers’ covenant before the battle of Blood River in December 1838 about which uncertainty has existed over the years concern the way it originated, the place where the vow has taken and the date, the content and wording, and its legitimacy or otherwise. By analysing the four most important sources regarding the covenant the author systematically attempts to provide clarity about some of these matters. It is pointed out that the version of the covenant given by G B A Gerdener in his book Sarel Cilliers, die vader van Dingaansdag, which was published in 1924, was obviously based on elements from the existing texts, with additions by Gerdener himself, and that it is misleading. The way that the covenant was celebrated since 1838 is examined and the question is briefly addressed as to who is bound by the covenant and what the intent of Sarel Cilliers and other participants in the event of 1838 was in this regard.